Distal Radial and Transpedal Access for Iliac Artery Chronic Total Occlusion Recanalisation using the Rendezvous Technique - Csavajda, Ádám; Deák, Mónika; Domsik, Péter; Ruzsa, Zoltán (Archives of Clinical and Medical Case Reports, 2019)
Distal radial artery access with combination of the transpedal access has not been published in the literature for iliac artery chronic total artery occlusion (CTO) recanalisation. A 70-years-old male patient with critical limb ischaemia was presented for iliac artery CTO recanalisation. The distal radial artery was punctured by ultrasonography guidance and the anterograde recanalisation was started from radial artery access, but due to the failed reentry the retrograde recanalisation was done from transpedal access and the retrograde reentry was performed with Rendezvous-technique using dual balloon inflations. Iliac artery stent implantation was done from transpedal access using 6F slender sheath with the good angiography result.